(untitled) (Journal of Hama University, 2025)
This research aims to study the relation between adduction, delaying and syntax in Al khteeb Al Sharbenys explanation : Al Serage Al Moneer in Understanding the Meaning of Words of Allah Al Hakeem Al khabeer . It is asyntactic and rhetorical study which gives the target . The research begins with the definition of the syntax , adduction and delaying in linguistic and idamatic way , then reffering to the meanigs which explain the syntax of the adduction which should be delayed and the opposite is right . Al Sharbeny has aimed in his explanation to employ the syntax to clarify the meaning which facilitates the reads to understand the verses in a scientific style . AlSharbeny was one of the grammarairs who has aimed to explain the Quran and the verses by connecting between syntax and semantics I clarify all these points in my study which explains the connection between adduction , delaying and syntax in Al Quran verses .